Global Comparisons of NmF2 anh hmF2 parameters between Ionosondes and Formosat-3/COSMIC satellites - Tam, Dao Ngoc Hanh; Chu, Yen-Hsyang (Vietnam Journal of Earth Sciences, 2012)
Formosat-3/COSMIC (F3/C) satellites were launched successfully in April 2006. The availability of F3/C GPS RO then have available for many researches. In this study, 3-year data of F3/C and global ionosonde stations were compared and analyzed. The F3/C electron density profiles were first preprocessed by data quality control schemes to ensure the good data for further comparisons. The F2 layer parameters observed by ionosonde experiments were then collected at the same time and collocated with the F3/C measurements to find out the differences between them.This work primarily focuses on the latitudinal differences between those two techniques. In the global comparison, four regions were separated including ±100 (equatorial region); ±100 to ±300 (near EIA crest regions); ±300 to ±500 (mid latitude regions); ±500 to ±900 (high latitude regions) in geomagnetic latitude degrees. Two parameters NmF2 and hmF2 of electron density profiles were compared and validated.Our results showed that NmF2 retrieved by F3/C and Ionosonde are in good agreement in general. The deviation was about 5%. In some regions, the correlation between two techniques is low since some unusual data retreived from Ionosonde exist. On the other hand, the uncertainty of NmF2 in the southern hemisphere was better than the conjugate regions in the northern hemisphere. As per as the hmF2 is concerned, the values determined from ionosonde were higher than F3/C, especially in mid and high latitudes. The lack of hmF2 data in low-latitude and equatorial regions was a problem in this comparision.